1965
DOI: 10.1001/archneur.1965.00470010088012
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Agnosia Without Aphasia

Abstract: cases of agnosia for sound and music have been reported for more than 80 years,1-10 such defects were invariably observed to be associated with at least a mild impairment in language recognition, ie, auditory verbal agnosia. According to Nielsen,11 only one case of an agnosia for sounds without evidence of aphasia either in the history or in the present clinical picture has so far been on record. This patient was a 52-year-old Mexican man who was examined with the aid of an interpreter.12 An older vascular les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
5

Year Published

1978
1978
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(49 citation statements)
references
References 5 publications
3
41
0
5
Order By: Relevance
“…Activation studies demonstrated that categorization of environmental sounds involves more specifically left prefrontal, temporal, parietal and cingulate regions (Engelien et al 1995), and our current studies have demonstrated that recognition of environmental sounds involves bilaterally regions on the temporal and prefrontal convexities (Maeder et al 2001). The ability to recognize environmental sounds was found to be deficient following right hemispheric lesions (Spreen et al 1965;Assal and Aubert 1979;Fujii et al 1990;Clarke et al 1996). Combined deficits of recognition of verbal and non-verbal sounds were reported in cases of bilateral (Albert et al 1972;Motomura et al 1986;Mendez and Geehan 1988;Buchtel and Stewart 1989) or unilateral left lesions (Pasquier et al 1991;Clarke et al 2000).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Activation studies demonstrated that categorization of environmental sounds involves more specifically left prefrontal, temporal, parietal and cingulate regions (Engelien et al 1995), and our current studies have demonstrated that recognition of environmental sounds involves bilaterally regions on the temporal and prefrontal convexities (Maeder et al 2001). The ability to recognize environmental sounds was found to be deficient following right hemispheric lesions (Spreen et al 1965;Assal and Aubert 1979;Fujii et al 1990;Clarke et al 1996). Combined deficits of recognition of verbal and non-verbal sounds were reported in cases of bilateral (Albert et al 1972;Motomura et al 1986;Mendez and Geehan 1988;Buchtel and Stewart 1989) or unilateral left lesions (Pasquier et al 1991;Clarke et al 2000).…”
Section: Introductionsupporting
confidence: 53%
“…There are three reports of auditory agnosia without auditory localization deficits (Spreen et al 1965;Jerger et al 1972;Fujii et al 1990) following right or bilateral lesions. Selective impairment in auditory motion perception was reported in one case following a right hemispheric lesion that included the insula and parietal convexity (Griffiths et al 1996(Griffiths et al , 1997.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore eliminated our third criterion, thereby broadening our search and adding another 27 cases of auditory agnosia (Albert and Bear, 1957;Baddeley and Wilson, 1993;Buchtel and Stewart, 1989;Chocholle et al, 1975;Clarke et al, 2000;Engelien et al, 1995;Fujii et al, 1990;Fung et al, 2000;Gazzaniga et al, 1974;Godefroy et al, 1995;Goldstein et al, 1975;Jerger et al, 1972;Kazui et al, 1990;Lambert et al, 1989;Metz-Lutz and Dahl, 1984;Motomura et al, 1986;Nové-Josserand et al, 1998;Oppenheimer and Newcombe, 1978;Reinhold, 1950;Roberts et al, 1987;Saffran et al, 1976;Spreen et al, 1965;Takahashi et al, 1992;von Stockert, 1982;Wohlfart et al, 1952). These cases included patients who had verbal auditory agnosia but could still speak; these patients are analogous to HJA, the aforementioned visual agnosic who could draw flowers.…”
Section: Neuropsychological Datamentioning
confidence: 99%
“…In addition, insula lesions often manifest as deficits in sound or speech recognition (auditory agnosia) and speech production (Spreen et al, 1965;Cancelliere and Kertesz, 1990;Engelien et al, 1995;Habib et al, 1995). Despite this evidence for a central role of the insula in processing and representing vocal communication sounds, little is known about the underlying neuronal substrate.…”
Section: Introductionmentioning
confidence: 99%